2005
DOI: 10.1111/j.0022-1112.2005.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Macquaria ambigua, in the Murray River, south‐eastern Australia

Abstract: A 2 year (2000)(2001) radio-tagging study was undertaken to investigate the movements of 51 golden perch Macquaria ambigua in the Murray River at Nyah in north-western Victoria, Australia. During the winter of both years, golden perch did not undertake movements >5 km and displayed strong home range fidelity. In the first year of the study there was an increase in the distance of golden perch movement during late spring which coincided with increasing water temperature and river discharge. Nineteen golden perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 14 publications
9
96
0
Order By: Relevance
“…Small ranges have been found previously in this species based on a markrecapture study (Lintermans, 1998), and in river blackfish based on radio-tracking (Khan et al, 2004;Koster & Crook, 2008). Similar findings have been made with members of the closely related family Percichthyidae (Simpson & Mapleston, 2002;Crook, 2004;O'Connor et al, 2005;Thiem et al, 2008;Ebner & Thiem, 2009;Koehn et al, 2009). Lintermans (1998) concluded that limited movement by twospined blackfish was most likely due to a behavioural, not physical or mechanical, phenomenon, and that larger individuals appear to be more sedentary than smaller individuals.…”
Section: Discussionsupporting
confidence: 86%
“…Small ranges have been found previously in this species based on a markrecapture study (Lintermans, 1998), and in river blackfish based on radio-tracking (Khan et al, 2004;Koster & Crook, 2008). Similar findings have been made with members of the closely related family Percichthyidae (Simpson & Mapleston, 2002;Crook, 2004;O'Connor et al, 2005;Thiem et al, 2008;Ebner & Thiem, 2009;Koehn et al, 2009). Lintermans (1998) concluded that limited movement by twospined blackfish was most likely due to a behavioural, not physical or mechanical, phenomenon, and that larger individuals appear to be more sedentary than smaller individuals.…”
Section: Discussionsupporting
confidence: 86%
“…The relatively large-scale breeding and homing movements by M. ikei have also been reported for other Australian percichthyids including Maccullochella peelii (Reynolds 1983, Koehn et al 2009), Macquaria ambigua (Reynolds 1983, O'Connor et al 2005) and estuary perch Macquaria colonorum (Walsh et al 2012). All species have been reported to relocate large distances to breed before returning to the vicinity of their original home-site some months later.…”
Section: Movement Patternsmentioning
confidence: 55%
“…Upstream and downstream spawning migrations, of up to 2500 km, have been suggested to explain spring movements of tagged golden perch (Reynolds 1983;O'Connor et al 2005;Mallen-Cooper and Brand 2007). The present study adds another component to this model with the greatest proportion (94%) of golden perch being adult sized and 41% of these individuals were males in spawning condition.…”
Section: Effectiveness Of the Fishwaymentioning
confidence: 63%